Ekstraksi Daun Kapuk Randu (Ceiba pentandra Gaertn) dengan Pelarut Etanol - Nur Apriliani; Aziz Ardiansyah; Siswanti Siswanti; Sri Sudarmi (Seminar Nasional Teknik Kimia Kejuangan, 2016)
Kapok leaf contain many active compounds include saponins, flavonoids and phenols. The compounds has broad uses, as detergents, forming foam in fire extinguishers and shampoo industries, having hemolysis activity, and as the compounds used to remove kidney stones. The research aims to find out the influence of extraction temperature and ratio of kapok leaf with solvent to the concentration, and calculate the mass transfer coefficient (Kc). The extraction process was done using kapok leaf powder extracted with ethanol as a solvent in a three-neck flask with a mixer on the extraction temperature, the ratio of leaf with a solvent, and a particular time. To determine the concentration of extract in the solution , the extract was analyzed using a UV- Vis spectrophotometer. Mass transfer coefficient values obtained by optimization of the concentration of extract data at various times. From the results of research on the optimum extraction temperature of 70 ° C on the ratio of kapok leaf with solvent of 5 g / 350ml is obtained extract 0,62% of the weight of the leaf and mass transfer coefficient (Kc) 5,74.10-1 g solvent / min.mm2.